Evidence for Quantum Chemical Effects in Receptor-Ligand Binding Between Integrin and Collagen Fragments — A Computational Investigation With an Impact on Tissue Repair, Neurooncolgy and Glycobiology - Eckert, Thomas; von Cosel, Jan; Kamps, Benedict; Siebert, Hans-Christian; Zhang, Ruiyan; Zhang, Ning; Gousias, Konstantinos; Petridis, Athanasios K.; Kanakis, Dimitrios; Falahati, Konstantin (Frontiers in Molecular Biosciences, 2021)
Abstract The collagen-integrin interactions are mediated by the doubly charged Mg2+ cation. In nature this cation seems to have the optimal binding strength to stabilize this complex. It is essential that the binding is not too weak so that the complex becomes unstable, however, it is also of importance that the ligand-receptor binding is still labile enough so that the ligand can separate from the receptor in a suited environment. In the case of crystal growing for experimentally useful integrin-collagen fragment complexes it turned out that Co2+ cations are ideal mediators to form stable complexes for such experiments. Although, one can argue that Co2+ is in this context an artificial cation, however, it is now of special interest to test the impact of this cation in cell-culture experiments focusing on integrin-ligand interactions. In order to examine, in particular, the role cobalt ions we have studied a Co2+ based model system using quantum chemical calculations. Thereby, we have shown that hybrid and long-range corrected functional, which are approximations provide already a sufficient level of accuracy. It is of interest to study a potential impact of cations on the binding of collagen-fragments including collagens from various species because different integrins have numerous biological functions (e.g. Integrin – NCAM (Neural cell adhesion molecule) interactions) and are triggered by intact and degraded collagen fragments. Since integrin–carbohydrate interactions play a key role when bio-medical problems such as tumor cell adhesion and virus-host cell infections have to be addressed on a sub-molecular level it is essential to understand the interactions with heavy-metal ions also at the subatomic level. Our findings open new routes, especially, in the fields of tissue repair and neuro-oncology for example for cell-culture experiments with different ions. The field of glycobiology is directly addressed when focusing on integrin-ligand interactions in which interactions with poly sialic acid and the HNK-1 epitope play a crucial role.